Reel food : essays on food and film - Bower, Anne (Routledge, 2004)
This is the first book devoted to food as a vibrant andevocative element of film. It reads various films through their uses ofFood - from major "food films" like Babette's Feast andBig Night - to less obvious choices including TheGodfather trilogy and The Matrix